2002
DOI: 10.1128/jb.184.11.3122-3125.2002
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Borrelia burgdorferi Transcriptome in Ixodes scapularis during Feeding

Abstract: Borrelia burgdorferi gene expression within the guts of engorging Ixodes scapularis ticks was examined by use of differential immunoscreening and differential expression with a customized amplified library. Fourteen chromosomal genes involved in energy metabolism, substrate transport, and signal transduction and 10 (4 chromosomal and 6 plasmid) genes encoding putative lipoproteins and periplasmic proteins were preferentially expressed in engorging ticks. These data demonstrate a new approach to the global anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 25 publications
4
59
2
1
Order By: Relevance
“…consistent with previous observations that B. burgdorferi produces maximal levels of DPD/AI-2 during exponential phase, and increased expression of luxS during the period of rapid growth accompanying transmission from feeding tick vectors to mammalian hosts (Babb et al, 2005;Narasimhan et al, 2002). Thus, high metabolic states are accompanied by increases in three enzymic activities: (1) MetK, which increases cellular levels of the only known borrelial methyl donor, SAM; (2) Pfs, which detoxifies the product of SAM-dependent methylation reactions; and (3) LuxS, which produces DPD and homocysteine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…consistent with previous observations that B. burgdorferi produces maximal levels of DPD/AI-2 during exponential phase, and increased expression of luxS during the period of rapid growth accompanying transmission from feeding tick vectors to mammalian hosts (Babb et al, 2005;Narasimhan et al, 2002). Thus, high metabolic states are accompanied by increases in three enzymic activities: (1) MetK, which increases cellular levels of the only known borrelial methyl donor, SAM; (2) Pfs, which detoxifies the product of SAM-dependent methylation reactions; and (3) LuxS, which produces DPD and homocysteine.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have implicated the importance of RNA polymerase subunits s S and s N in B. burgdorferi transitional events, including transmission from tick to mammal Elias et al, 2000;Yang et al, 2000). Since the ORF BB0374-pfs-metK-luxS operon is induced during tick-to-mammal transmission (Narasimhan et al, 2002), we examined whether either s S or s N played a role in regulation of operon transcription. The s S subunit is induced as cultures approach stationary phase, and s S levels are dependent on s N Elias et al, 2000;Yang et al, 2000).…”
Section: Growth Rate Dependent Expression Of the Operonmentioning
confidence: 99%
“…Live imaging has revealed that this conception is an oversimplification. That Borrelia within unfed nymphal midguts are nonmotile is consistent with the quiescent metabolic state of organisms in this milieu (50)(51)(52)(53)(54) and is in line with observations made with crushed midguts dating back to the discovery of the Lyme spirochete as a tick-borne pathogen (49). On the other hand, our finding that the fed midgut is populated with replicating, but nonmotile, spirochetes was unexpected and runs counter to the prevailing notion, which equates metabolic activity with motility (58).…”
Section: Figuresupporting
confidence: 87%
“…After the meal is complete, within days the number of organisms drops precipitously and remains low until the next blood meal. Narasimhan et al have previously found that genes in the opp operon were differentially expressed in fed and unfed ticks but did not identify specific genes within the operon that accounted for the differences (13). We have found that expression of oppA-II and oppA-IV remains very low in the tick hosts and that oppA-III and oppA-V are up-regulated during periods of stable nutrient availability (unfed tick and mouse hosts).…”
Section: Discussioncontrasting
confidence: 56%